2020
DOI: 10.3390/d12030116
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity Distribution Pattern of Ruderal Community under the Rapid Urbanization in Hangzhou, East China

Abstract: The process of rapid urbanization has affected the composition and diversity of urban vegetation species. The process of urbanization from 2000 was analyzed in the area of "one major city with three vice cities and six groups", according to the urban master planning of Hangzhou from 2001 to 2020. The results show that dramatic changes have occurred for land use types during the ten years from 2000 to 2010 in Hangzhou, of which urban land has become the main type of land use and the area of arable land has pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Some studies showed that light pollution might affect migrations of moths (Boyes et al, 2020 ) and this factor is certainly important in the case of Rąbień. It might also explain the large number of typical herbal vegetation species, including many noctuids associated with ruderal plants ( Urtica , Plantago, Rumex, Taraxacum officinale ) that are normally rare or absent in forest ecosystems and peat bogs, but are very common in urbanized areas (Zhang et al, 2020 ) and might also expand in neighboring forests or peatbogs like Rąbień. It was already proven that light traps are an efficient tool for assessing local moth communities.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that light pollution might affect migrations of moths (Boyes et al, 2020 ) and this factor is certainly important in the case of Rąbień. It might also explain the large number of typical herbal vegetation species, including many noctuids associated with ruderal plants ( Urtica , Plantago, Rumex, Taraxacum officinale ) that are normally rare or absent in forest ecosystems and peat bogs, but are very common in urbanized areas (Zhang et al, 2020 ) and might also expand in neighboring forests or peatbogs like Rąbień. It was already proven that light traps are an efficient tool for assessing local moth communities.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid expansion of urbanization and urban renewal iterations have resulted in many problems, including a large amount of building waste, idle land, and abandoned factories [42,43]. During the process of abandonment or in idleness, the autophyte community naturally develops and gradually occupies a site.…”
Section: Protection and Management Of Shps In The Process Of Rapid Ur...mentioning
confidence: 99%
“…Hangzhou City is located on the East coast of China (Figure 1); it is the capital of Zhejiang province and a central city of the Yangtze River Delta. Hangzhou has a subtropical monsoon climate, with a mean annual precipitation of 1421.7 mm and a mean annual temperature of 16.2 • C [16,30]. The city has experienced rapid urbanization and increased energy consumption in response to economic and population growth since the 1980s.…”
Section: Study Areamentioning
confidence: 99%